Amitriptyline poisoning of a baby: How informative can hair analysis be?. (April 2015) - Allibe, Nathalie; Eysseric-Guerin, Hélène; Kintz, Pascal; Bartoli, Mireille; Bost-Bru, Cécile; Grenier, Florian; Scolan, Virginie; Stanke-Labesque, Françoise
Highlights: Case report of a baby intoxication with amitriptyline. Interpretation difficulties in hair testing, particularly in children are discussed. Interest of complement hair testing in child, family members and close circle. Rapid LC–MS/MS method with automated online sample clean-up. Quantification of AMI and NOR in hair from small amount of sample. Abstract: We reported a case of a 6-month-old baby girl who was hospitalized in the pediatric emergency for central nervous system disorders then coma. Toxicology analysis showed the presence of amitriptyline (AMI) and its metabolite nortriptyline (NOR) in blood and urine of the baby. Additional investigations suggested a shaken baby syndrome. Given the family context, a judge ordered hair tests for both the child and his parents to document drug exposure. A liquid chromatography tandem mass spectrometric (LC–MS/MS) method was then developed to quantify AMI and NOR in hair. After decontamination and segmentation, 20 mg of hair was incubated overnight at 55 °C in methanol (MeOH). The LC–MS/MS method used an online solid phase extraction and the analysis was performed using two transitions per compound. The LOQ and LOD for the two compounds were estimated at 0.0075 ng/mg and 0.005 ng/mg respectively. All hair segments tested for both parents were negative. For the baby two strands of hair were collected one day after the acute intoxication for the first and 5 weeks later for the second. The first strand was not decontaminated before analysis to avoid losing specimen. The high and relatively homogenous concentrations of AMI (with a range of value from 6.65 to 9.69 ng/mg) and NOR (with a range of value from 7.12 to 8.96 ng/mg) measured suggested that contamination could have occurred. The analysis of the second strand after decontamination allowed to detect AMI and NOR in all hair segments. The obtained values varied between 0.54 and 1.41 ng/mg for AMI and between 1.26 and 4.00 ng/mg for NOR. These results supported the hypothesis of a chronic exposure during several months before hair collection with regular increase. However a single overdose could not be totally excluded. The interpretation of results must take into account the pharmacological and physiological parameters of hair of the children.